Audience Reception Analysis Of Tolerance In The 'Login' Program Episode '6 Religious Leaders' On Deddy Corbuzier’s Youtube Channel - Fajar Muharam; Abi Fajar Ramadhan; Haryo Windratno; Ferrari Lancia (Asosiasi Dosen Muda Indonesia, 2025)
Advances in technology and information have clearly manifested with the emergence of various new media platforms that are widely utilized. One such platform is the social media platform YouTube, which is used for information dissemination. This is exemplified by the program